Lay Health Promoters Empower Neighbourhoods-Results From a Community-Based Research Programme in Southern Sweden - Rämgård, Margareta; Avery, Helen (Frontiers in Public Health, 2022)
This article focuses on the role of lay health promoters in the Lindängen initiative, a community-based participatory research (CBPR) programme for health promotion that started 2016 in a low-income neighbourhood in the outskirts of Malmö, Southern Sweden. The programme aimed to support equitable health and develop an innovative model for community health promotion. The purpose of this article is to describe the role of the lay health promoters in the initiative and discuss the challenges of their position mediating between residents of the neighbourhood and the established institutions, using interviews, meeting notes and focus groups sessions with the health promoters and local stakeholders. Lay health promoters’ role and function developed in a collaborative process of networking with local stakeholders and citizens in local meeting places. Their work was based on their credibility in their role, in combination with the use of a CBPR model that was open to innovation, with a strong focus on actively engaging members of the community. This allowed the lay health promoters to take political and social stances towards various issues, and to start to concretely address the social determinants of health in the community, as well as express recommendations to policymakers. Based on these experiences, the lay health promoters gained clearer insights into the institutional and structural conditions that impact their community. The position they had in the process of the programme resulted in empowerment and a new local association for health promotion; LindängenKraft (LindängenPower) driven by the health promotors and community members.